PENJAMINAN MUTU DAN KEHALALAN PRODUK OLAHAN SUSU - Octaviannus Amen; Aji Jumiono; Mohamad Ali Fulazzaky (Universitas Djuanda, 2020)
Quality assurance and halalness of processed milk products must be started from the process of producing cow's milk on farms to the distribution process and its direct use by consumers or for industrial use. In the process of processing milk that is processed into various processed milk products in the form of cheese, yoghurt, ice cream, and butter, it has a critical point of halalness. The source of additional materials used during the product processing process is the main critical point for its halalness. The use of additives such as sugar as a sweetener, microbial starter culture for the fermentation process, coloring, flavor, and fatty acids as emulsifiers are examples of critical points for materials that the sources can from non-halal animal materials or halal animals that are not slaughtered according to Islamic law.